The effects of social vs. personal power on universal dimensions of social perception - Lai, Linda (Frontiers in Psychology, 2023)
The present study expands previous research on the effects of power on stereotyping by investigating the impact of two types of power (social power and personal power) on two universal dimensions of social perception; warmth and competence. Results from an experiment (N = 377) in which participants were randomly assigned to provide their impression of either (1) poor people or (2) rich people, suggest that the two types of power produce different effects on perceptions of warmth and competence. Personal power increased stereotype consistent perceptions of warmth whereas social power increased stereotype consistent perceptions of competence as well as agency, which was identified as a separate dimension. The pattern of results is discussed in view of previous work on power effects and stereotyping, and potential explanations and suggestions for future research are outlined.